Численное моделирование процесса релаксацииквантово-тепловыхфлуктуаций - Golubjeva, O. N.; Sidorov, S. V.; Bar’yakhtar, V. G. (Publishing house "Academperiodika", 2019)
A generalization of quantum-mechanical equations expressed in the hydrodynamic form by introducing terms that involve the diffusion velocity at zero and finite temperatures, as well as the diffusion pressure energy in a warm vacuum, into the Lagrangian density has been proposed. It is used as a basis for constructing a system of equations similar to the Euler equations, but making allowance for quantum-mechanical and thermal effects, for the model of one-dimensional hydrodynamics. The equations obtained generalize the equations of the Nelson stochastic mechanics. A numerical analysis of the solutions of this system allowed a conclusion to be drawn about its validity for the description of the relaxation of quantum thermal fluctuations.